A relação entre Eros e Areté n’ O Banquete de Platão - DIAS, Vanessa da Silva (2024)
The Banquet is one of Plato's best-known works and has been the subject of research over the years in the academic world on various themes, the main one being the discussion of eros. In view of this, the purpose of this research was to investigate the relationship between eros and areté in this work. It is common ground that eros is the central theme of this dialogue, unlike areté, whose presence in the debate is not so evident. Thus, our research is justified by the search for a more detailed analysis of areté in the dialogue, since it has an intrinsic relationship with eros that has not yet been problematised in more detail. To this end, we will demonstrate the faces of eros present in the five speeches (Phaedrus, Pausanias, Erixymachus, Aristophanes and Agathon) that precede Socrates' speech, seeking to highlight the presence of areté in each of them. Next, we'll present the discussion that runs through the dialogue of Ménon, with areté specifically as its theme, because it's necessary to contextualise this second concept that we're working with, just as it is with the first. We will also work on the last two speeches: firstly, Socrates, who seeks the help of the priestess Diotima of Mantineia, who once taught him about the things of love (eros); and then, the speech of Alcibiades, who, through his overwhelming and immediate passion, recounts his unsuccessful attempts to win over the great Socrates.